Fasting inhibits excitatory synaptic input on paraventricular oxytocin neurons via neuropeptide Y and Y1 receptor, inducing rebound hyperphagia, and weight gain - Wang, Lei; Suyama, Shigetomo; Lee, Samantha A.; Ueta, Yoichi; Seino, Yutaka; Sharp, Geoffrey W. G.; Yada, Toshihiko (Frontiers in Nutrition, 2022)
Fasting with varying intensities is used to treat obesity-related diseases. Re-feeding after fasting exhibits hyperphagia and often rebound weight gain. However, the mechanisms underlying the hyperphagia and rebound remain elusive. Here we show that 24 h food restriction (24 h FR) and milder 50% FR, both depress synaptic transmission in the hypothalamic paraventricular nucleus (PVN) and induce acute hyperphagia in rats. 24 h FR is followed by weight rebound but 50% FR is not. Orexigenic neuropeptide Y (NPY) via the Y1 receptor (Y1R) inhibited the miniature excitatory postsynaptic current (mEPSC) on anorexigenic oxytocin neurons in the PVN. 24 h FR and 50% FR activated this neuronal pathway to induce acute hyperphagia on Days 1–3 and Days 1–2 after FR, respectively. 24 h FR induced large mEPSC depression, recurrent hyperphagia on Days 9–12 and rebound weight gain on Days 12–17, whereas 50% FR induced moderate mEPSC depression and sustained weight reduction. Transverse data analysis on Day 1 after 24 h FR and 50% FR demonstrated saturation kinetics for the mEPSC depression-hyperphagiacurve, implying hysteresis. The results reveal FR-driven synaptic plasticity in the NPY-Y1R-oxytocin neurocircuit that drives acute hyperphagia. FR with the intensity that regulates the synapse-feeding relay without hysteresis is the key for successful dieting.